STUDIES ON THE PHYTOPLANKTON IN PILLI RESERVOIR, NEAR REHAR TOWN (BIJNOR), UTTAR PRADESH - RAUTHAN, J.V.S.; KUMAR, DINESH; RAUTHAN, GEETA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
Distribution of phytoplankton in Pilli Reservoir was studied during 2005-06 to assess the trophic status. The reservoir supported low phytoplankton population. The seasonal abundance of phytoplankton ranked in the following order — winter> summer> rainy season. Total population of phytoplankton varied from 2565 uI1 and 5581 ul with lowest and highest population being formed during August and October respectively. A total of 25 species of phytoplankton were collected from all sectors of the reservoir including Chlorophyceae (10), Bacillariophyceae (2) and Myxophyceae (3).